Governance Strategy Juridical Rural Creative Economy Respond To Competitive Global Competition - Adnyani, Ni Ketut Sari; Sudiatmaka, Ketut; Landrawan, I Wayan (Universitas Tabanan, 2022)
This research is motivated because of the importance of legal protection also serves as protection for the governance of the rural economy, among others, can we review the various forms of business startups together or independent creative such as from several sectors among others include: crafts produced by businesses traditional craft